KINDNESS BRINGS LIGHT AND UNLIMITED JOY TO THE HUMAN HEART (Academia Science Repository, 2023)
When you see a person with sad eyes, but a smile on their face, you involuntarily know a flaw or problem. It is a duty for each of us to take care of a person who has a problem in life, to be kind to him. A good deed, a little attention brings light and infinite joy to their hearts. It is a great happiness to be able to receive information about the condition of people with disabilities, weak hearts, to instill trust and hope in others, to give comfort and joy to hearts that are thirsty for love.